Production of Solid Soap from Arabica Coffee Grounds (Coffea arabica L.) with Antibacterial Properties - Ni Made Sukma Sanjiwani; Komang Ariani; I Made Agus Sunadi Putra; I Wayan Surya Rahadi; Ni Putu Ayu Mirah Mariati; I Wayan Sudiarsa; Ni Nyoman Wahyu Udayani (Journal of Food and Pharmaceutical Sciences, 2026)
Coffee shops are now a favourite hangout for people of all ages, so many entrepreneurs are developing coffee shop businesses because of their high profit potential. Arabica coffee is the type of coffee most commonly used in coffee shops. The coffee-making process produces waste in the form of coffee grounds. Coffee grounds can be used as an ingredient in beauty products such as soap. Soap is the result of saponification, which is a reaction between a base or alkali and fatty acids, which acts as a skin cleanser. This study aims to examine the presence of secondary metabolite compounds in Arabica coffee grounds (Coffea arabica L.), test the physical quality of solid soap made from Arabica coffee grounds (C arabica L.), and assess the soap's ability to inhibit the growth of Staphylococcus aureus bacteria. Arabica coffee grounds were first analysed through qualitative phytochemical screening tests using test tubes and various reagents, then formulated into solid soap with different concentrations, namely 4%, 7%, and 9%. After that, physical properties testing and antibacterial activity evaluation against Staphylococcus aureus were carried out using the disc diffusion method. The research results data were presented using descriptive analysis. The tests revealed that Arabica coffee residues contain secondary metabolites in the form of alkaloids, flavonoids, tannins, saponins, and triterpenoids. Solid soap made from Arabica coffee grounds meets the physical quality test standards in accordance with SNI 3532:2021 and that solid soap made from Arabica coffee grounds with a percentage of 7% (formula 2) and 9% (formula 3) has the potential to inhibit the activity of Staphylococcus aureus bacteria with a moderate category. It can be concluded that Arabica coffee grounds contain secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and triterpenoids. Solid soap with Arabica coffee grounds as an ingredient meets the physical quality requirements in accordance with SNI 3532:2021. Soap formulas with a coffee grounds concentration of 7% (F2) and 9% (F3) have the potential to inhibit the growth of Staphylococcus aureus with moderate efficacy.